Mitochondrial genome complexity in Stemona sessilifolia: nanopore sequencing reveals chloroplast gene transfer and DNA rearrangements - Xie, Yuning; Liu, Wenqiong; Guo, Liwen; Zhang, Xuemei (Frontiers in Genetics, 2024)
Mitochondria are semi-autonomous organelles in eukaryotic cells with their own genome. Plant mitogenomes differ from animal mitogenomes in size, structure, and repetitive DNA sequences. Despite larger sizes, plant mitogenomes do not have significantly more genes. They exhibit diverse structures due to variations in size, repetitive DNA, recombination frequencies, low gene densities, and reduced nucleotide substitution rates. In this study, we analyzed the mitochondrial genome of Stemona sessilifolia using Nanopore and Illumina sequencing. De-novo assembly and annotation were conducted using Unicycler, Geseq, tRNAscan-SE and BLASTN, followed by codon usage, repeat sequence, RNA-editing, synteny, and phylogenetic analyses. S. sessilifolia’s mitogenome consisted of one linear contig and six circular contigs totaling 724,751 bp. It had 39 protein-coding genes, 27 tRNA genes, and 3 rRNA genes. Transfer of chloroplast sequences accounted for 13.14% of the mitogenome. Various analyses provided insights into genetic characteristics, evolutionary dynamics, and phylogenetic placement. Further investigations can explore transferred genes’ functions and RNA-editing’s role in mitochondrial gene expression in S. sessilifolia.